2016
DOI: 10.1038/bmt.2016.2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between neurocognitive functioning and medication management ability over the first 6 months following allogeneic stem cell transplantation

Abstract: Although neurocognitive impairment has been established as a major issue among cancer survivors, the real-world consequences of this impairment are unclear. This study investigated the relationship between neurocognitive functioning and medication management ability over time among 58 patients treated with allogeneic hematopoietic stem cell transplantation (HCT). Participants completed a neuropsychological test battery and a simulated medication management task at three time points: pretransplant (T0), Day 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 50 publications
0
15
0
1
Order By: Relevance
“…10 Similarly, Booth-Jones and colleagues noted significant relationships between fatigue and depression and neurocognitive dysfunction in a cohort of patients at least six months following HCT. 30 However, it should be noted that two studies found no significant relationship between fatigue or depression and neurocognitive dysfunction, 19,29 and that two other studies found anxiety to be significantly associated with neurocognitive dysfunction. 30,113 …”
Section: Correlatesmentioning
confidence: 95%
See 2 more Smart Citations
“…10 Similarly, Booth-Jones and colleagues noted significant relationships between fatigue and depression and neurocognitive dysfunction in a cohort of patients at least six months following HCT. 30 However, it should be noted that two studies found no significant relationship between fatigue or depression and neurocognitive dysfunction, 19,29 and that two other studies found anxiety to be significantly associated with neurocognitive dysfunction. 30,113 …”
Section: Correlatesmentioning
confidence: 95%
“…In this area of research, most studies have focused on fatigue and depressive symptoms. 10,19,29,30 For example, one longitudinal study examined cancer-related symptoms associated with neurocognitive dysfunction and found significant relationships over time among several domains of neurocognitive function and symptoms such as fatigue, depression, and perceived stress. 113 Another study examined patients with multiple myeloma who completed autologous HCT and found similar associations between neurocognitive function and symptoms (e.g.…”
Section: Correlatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, higher incidences of anxiety, fatigue, depression, emotional distress, and poor physical and social functioning have also been reported among HCT survivors with neurocognitive dysfunction [10,25]. These side effects may lead to difficulty with medication management, including dosing errors and noncompliance, in the early period after HCT [40].…”
Section: Neurocognitive Issues In Adultsmentioning
confidence: 99%
“… 1 2 CRCI is typically characterised by problems in memory, attention, processing speed and executive functioning. 3 4 The potential consequences of CRCI on survivors’ quality of life are significant, including challenges with emotional well-being, return to work and ability to engage effectively in self-care 5 6 in the months to years after treatment.…”
Section: Introductionmentioning
confidence: 99%